Experimental study on a sampling technique based on a freeze-sediments valve for deep-sea microorganism. (January 2019) - Li, Yanliang; Peng, Jianming; Huang, Chaoyang; Wang, Maosen
Abstract: Deep-sea microorganism research has become a hot topic in life science, owing to its special value in high pressure and low temperature environment. If not kept the in-situ low temperature and high pressure, it will cause the microorganism to lose its activity and lead to a waste of resources. A freeze-sediments valve presents a promising solution to maintain the low temperature and high pressure in situ, improve the success rate of sampling and shorten the sampling time. A series of experiments were conducted to characterize the freeze-sediments valve, including the sampling time without leakage, adaptation to different sediments and the effect of the length, etc. Most important of all, temperature change of sediments is observed in all experiments. Experimental results indicated that the freeze-sediments valve was formed in 5 min without leakage and the freeze-sediments valve could be applied to different sediments without limitations on sediments type and mineral content. Considering the pressure retaining capacity and formation time of freeze-sediments valve, it was found that the freeze-sediments valve with a length of 60–80 mm has good pressure retaining capacity whose value was 41.3–48.4 Mpa and short formation time which was 5 min. Precooling the sampler could be used to shorten the sampling time in the actual environment application. This sampling technique can play a vital role in maintaining in-situ low temperature at −2 to −4 ° Celsius in all the experiments. According to the tests, the sampling technique based on the freeze-sediments valve had the potential to solve the problem of keeping in-situ temperature, low sampling success rate and long sampling time in the future.